MODEL OF GROWTH OF SETTLEMENT AREAS IN JAMBI CITY - Cahyadi Nugroho; Nismawati Nismawati (Remote Sensing Technology Study Program, 2020)
This study illustrates the growth model of Jambi City until 2035 supported by several driving factors derived from human activities and patterns of movement. Sampling based on the administrative Area of Interest (AOI) of Jambi City. Sources of data obtained from relevant agencies and remote sensing imagery (Landsat Image). Analysis of research data using demographic analysis, GIS, Cellular Automata and statistics. The results showed that there was a change in land cover during the predictions between 2016-2035; Judging from the growth of settlements, each year it is increasingly referring to the expansion diffusion model with concentric shapes through Cellular Automata modeling. Settlements will always grow in the Central Business District, namely Pasar Jambi District and Jelutung District and South Jambi District will further develop in 2035.